Magical realism in selected works of Marquez and Morrison - Shabrang, Hoda (2013)
This research argues that Marquez’s One Hundred Years of Solitude, Last Voyage of the Ghost Ship, The Ghosts of August, and Morrison’s Beloved and,Paradise draw from the magical realist elements, in particular, ghosts, to respond to the twisted histories that they respectively address. Even though they are very different, all these works expand and extend the ghost or ghosted figures in a similar direction. We can see through all these works how ghosts assist characters to look at their inner truth in society or in themselves. They are concerned about the history of oppression and rejection as well as colonialism, dependence and its aftermath by using the haunting figure of the ghosts. In other words, they are all engaged with traumatic historical realities which are revealed or embodied in the magical realist element of ghost. In all selected works, Marquez andMorrison exploit the magical realist element,the ghost, and its liminal power of spectrality to transfer the personal memories and cultural histories as well as “unghosting” silenced, marginalized characters who are social outcasts. According to Derrida, what evokes the ghost in the first place is injustice, which is the result of hegemony. He believes the spectral intercedes on behalf of a dominated, oppressed class in society. However, what we see in these works is a correlation between dominant oppression, which leads to injustice. The ghosts provide the connecting bridge between characters past and present, while also assisting them to shift their perspectives of self and the world around them. In Marquez’s works, ghosts come back because they are evoked by the oppression of hegemonic power. Although Marquez’s ghosts are embodiments of memories and try to save and warn other characters, their attempts remain futile. Indeed, the history of the Buendia family is founded on violence, fratricide, rape and hegemony, all of which are but a reflection of Colombian and much of Latin American history – episodes such as the Civil War and the banana company massacre are based on real events that occurred in Colombia. Although Marquez closes One Hundred Years of Solitude with the destruction of the Buendia family and their village of Macondo, ravaged by an apocalyptic hurricane, the ending Morrison chooses for her story is dominated by a feeling of optimism. In studying Beloved and Paradise, this research revealsthe expansive places between the rigid oppression drawn among classes, genders, magic and reality,past and present, life and death. The tools for this liminal journey encompass ghost figures. Morrison’s ghosts bring attention to veiled and blurred spots in history, those locations where mainstream America does not shine light on. Morrison bestows presence, and voice on the ghosted, silenced, and the oppressed on the margins of society who are ignored a space in which to tell the story of their experiences. Surprisingly in Morrison’s novels, ghost acts not only as a bridge between past and present to help ghosted characters digest and comprehend their painful past, but also as a guidance which leads them out of their stagnant situation and finally heals and empowers each one of these marginalized individuals.